STUDY OF THE INFLUENCE OF LIGHT ON A SEMICONDUCTOR PHOTOELEMENT (Scientific journal of the Fergana State University, 2025)
The article presents information on the creation of highly efficient photovoltaic elements due to the effective use of the spectral composition of solar radiation. The results of studies on the creation of flat multilayer photovoltaic cells with several energy levels of longitudinal and transverse nature from thin films of chalcogenides are presented. The universal properties of such photovoltaic elements are revealed and a system is created that is capable of working with both conductive and dielectric consumers. The consumer of photovoltaic elements is a metal that uses the monochromaticity of the light spectrum to ensure high voltage and energy transfer efficiency.